Judicial perspectives on the sentencing of minor drug offenders in Indonesia: discretionary practice and compassionate approaches - Hamilton Smith, Niall (2020)
This paper explores the perceptions of Indonesian Judges in sentencing minor drug offenders. The Judge holds a central role in the administration of justice and, because of the significance of judicial discretion, it is essential to understand how judges come to their sentencing decisions. To develop an understanding of what judges are trying to achieve when sentencing minor drug offenders, a total of 31 judges were interviewed: 28 participants came from District Courts in Urban and Rural jurisdictions in Indonesia (17 from Urban Courts and 11 from Rural Courts) and three were Supreme Court judges. The findings highlight that the process of justice involves not merely the application of the rule of the law or relevant legal codes; rather, how the judiciary balance and interpret the law is a central part of court sentencing practice